A wearable skin stretch haptic feedback device: towards improving balance control in lower limb amputees - Husman, Muhammad Afif; Maqbool, H. F.; Awad, M. I.; Abouhossein, Alireza; Dehghani-Sanij, A. A. (IEEE, 2016)
Haptic feedback to lower limb amputees is essential to maximize the functionality of a prosthetic device by providing information to the user about the interaction with the environment and the position of the prostheses in space. Severed sensory pathway and the absence of connection between the prosthesis and the Central Nervous System (CNS) after lower limb amputation reduces balance control, increases visual dependency and increases risk of falls among amputees. This work describes the design of a wearable haptic feedback device for lower limb amputees using lateral skin-stretch modality intended to serve as a feedback cue during ambulation. A feedback scheme was proposed based on gait event detection for possible real-time postural adjustment. Preliminary perceptual test with healthy subjects in static condition was carried out and the results indicated over 98% accuracy in determining stimuli location around the upper leg region, suggesting good perceptibility of the delivered stimuli.